SUSTAINABLE AGE FRIENDLY TOURISM DEVELOPMENT ASSESSING INFRASTRUCTURE AND ELDERLY MOBILITY IN PENANG, MALAYSIA - Musa, Norizan; Yusoh, Mohamad Pirdaus; Nik Hashim, Nik Alif Amri; Zulkefli, Nor Syuhada; Nasir, Muhamad Nasyat Muhamad (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
Penang’s population is changing, with an increase in the elderly. This study examines the with a focus on the consequences for mobility and infrastructure. The objectives are to identify the infrastructural needs of elderly tourists, assess the effectiveness of current policies, and propose enhancements to foster an inclusive tourism environment. Employing a qualitative methodology, the research involved in-depth interviews with 15 stakeholders, including government officials, urban planners, tourism operators, and elderly community representatives. Data were analyzed thematically to extract key insights related to accessibility, transportation, and service provision for elderly tourists. The results show that although Penang has taken a number of steps, including the Age Friendly City project and the incorporation of universal design principles in public infrastructure, difficulties still exist. Elderly visitors’ mobility and general experience are hampered by problems like poor pedestrian walkways, few public transportation options, and inadequate signage. To properly serve the senior population, tourist staff members also require specialized training. This study complements on sustainable tourism development by offering stakeholders and policymakers evidence-based suggestions. It emphasizes how crucial inclusive planning is to improving senior citizens quality of life and establishing Penang as a top age-friendly travel destination.